Increased risks of Maternal Mental Health Conditions Following the COVID-19 Pandemic - Anita Zhou; Allison Zetterman; Megan Ott; Colman Freel; Kayla Adams; Andrea Rodriguez-Dasta; Rebekah Rapoza; Rebecca Drakowski; Sarah Sweeney; Alyssa Freeman; Matthew VanOrmer; Melissa Thoene; et al. (Women's Health Reports)
Background: Women are at an increased risk of developing psychiatric conditions such as anxiety and depression during pregnancy. Psychiatric conditions during pregnancy can put mothers and fetuses at risk of worse physical and mental health before, during, and after the completion of a pregnancy. Previous research indicates that women pregnant during COVID-19 were at a greater risk of developing mental health conditions and being exposed to stressors. While most of the research in the field focuses solely on maternal mental health or interactions between stressors and maternal mental health, little research has been done comparing maternal mental health, demographic variables, and socioeconomic variables across pre-, during-, and post-COVID-19 time periods. Methods: We conducted an observational cohort study of 703 mothers divided into pre-, during-, and post-COVID-19 groups based on time of enrollment. Results: Rates of maternal anxiety (p < 0.001), medication use for anxiety (p < 0.001), depression (p < 0.001), medication use for depression (p < 0.001), history of postpartum depression (p < 0.001), and medication use for other psychiatric conditions (p < 0.001) significantly increased during COVID-19 and remained at elevated levels post-COVID-19 compared with pre-COVID-19. Income >150% of the poverty level (p = 0.003), food security level (p = 0.010), marital status (p = 0.001), and private insurance type (p < 0.001) were significantly increased during COVID-19 compared with pre-COVID-19 levels. Conclusions: Future work should focus on stratifying the effects of the COVID-19 pandemic on maternal mental health by race and ethnicity and establishing guidelines to support maternal mental health during epidemics and pandemics.